Science for the people: The climate justice approach. President Mary Robinson - Robinson, M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
Introduction: Lindiwe Sibanda. Speaker: Mary Robinson, President, The Mary Robinson Foundation for Climate Justice (MRFCJ), former President of Ireland and United Nations High Commissioner for Human Rights.